2022
DOI: 10.3389/fpsyg.2022.922211
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Impact of Competitive Advantage and Core Competency on Regional Tourism Revitalization: Empirical Evidence in Taiwan

Abstract: Competitive advantage and core competency are the unique capabilities and assets of an organization to provide valuable products or services to customers, thus giving the organization a better competitive position in the market than its competitors. In addition, how to create a competitive advantage is also one of the main objectives of business strategy. Therefore, this study focuses on understanding the decisive factors in regional revitalization and the relationship between business strategy, strategic alli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 134 publications
0
8
0
Order By: Relevance
“…Prior research argued that exceptional customer service can differentiate tourism products from others in the market (Ko et al, 2023), high-quality customer service creates a positive and memorable experience for tourists (Moliner-Tena et al, 2023;Zhou et al, 2023), and indicated customer service capabilities of enterprises and their competitive advantage in the tourism industry is highly significant (Lee et al, 2022).…”
Section: 26mentioning
confidence: 99%
“…Prior research argued that exceptional customer service can differentiate tourism products from others in the market (Ko et al, 2023), high-quality customer service creates a positive and memorable experience for tourists (Moliner-Tena et al, 2023;Zhou et al, 2023), and indicated customer service capabilities of enterprises and their competitive advantage in the tourism industry is highly significant (Lee et al, 2022).…”
Section: 26mentioning
confidence: 99%
“…Organizational innovation through significantly upgraded business practices, and stakeholder relationships enhances company performance. Competitive advantage is the capability of a company to influence its distinct capabilities and resources in providing valuable commodities to customers which enables them to attain advantageous competitive position than competitors in the industry (Lee et al, 2022). According to Udriyah et al (2019), competitive advantage is the pool of resources which offer an exceptional and higher position for companies to differentiate themselves from their rivals in the marketplace.…”
Section: Introductionmentioning
confidence: 99%
“…Huang and Liu (2019) pointed out that when creativity increases, service innovation is further strengthened. Lee et al (2022) pointed out that competitive advantage, core competitiveness, and strategic alliance partner selection have significant effects on alliance performance. This study attempts to explore hospitality options and green brand restaurant alliances or self-created brand specialty restaurants.…”
Section: Introductionmentioning
confidence: 99%